DIET AND GENERATION Z PERSONALITY: A SEMIOTIC ANALYSIS OF YULIA BALTSCHUN’S YOUTUBE CONTENT - Angelica, Aurel; Yunus, Ulani; Rubiyanto (JURNAL SIGNAL, 2025)
This study analyzed the diet failure of Generation Z through the lens of Roland Barthes's semiotic analysis using Yulia Baltschun's YouTube content as a case study. The purpose of this study is to identify the meanings shown through the symbols contained in Yulia Baltschun's YouTube account. The research method used is Roland Barthes's semiotic analysis. The results obtained show that the meaning of the denotation displayed on Yulia Baltschun's YouTube account is through diet, exercise patterns, and daily habits. The meaning of the connotation that can be explored from Yulia Baltschun's YouTube account is that a person's attitude in living life determines the success of their diet. In conclusion, revealing the symbols revealed on Yulia Baltschun's account give insight to those who want to have an ideal body with healthy habits. The study also highlights the importance of semiotic analysis in understanding the implicit messages conveyed by influencers on social media. Additionally, the study emphasizes that the interpretation of the meaning of these symbols can vary depending on the cultural background and personal experiences of the audience.